Lirismo e homoerotismo n´As Canções de António Botto - Andrade, Rosevan Marcolino de (2012)
The focus of this research was to discuss the materialization of the homoerotic desire and lyricism in As canções de António Botto. Firstly, we researched about the theory of lyric according to the studies of Adorno (2003), Pound (2006), Staiger (1975), Lima (1975), and others; other sources about the homoerotism from Barcellos (2006) and Silva (2007, 2008) were made. Thus, we intend to present an interpretation on Botto's poems in order to analyse the following: how does the poetic language means act in order to construct the homoerotic relationships in As Canções de António Botto? Consequently, we chose the poems from the chapters Olimpíadas, Adolescente, Ciúme e Curiosidades Estéticas to emphasize the presence of the homoerotism theme, focusing the semantic and imagery constructions that embody this theme in the poems. As a theorical complement on homosexual relationships from Greek period, we chose Foucault (2007a, 2007b, 2007c), Dover (2007) e Ullmann (2005). Finally, we analysed how the body language is set as an object of desire in homoerotic relationships in As Canções de António Botto. The body is considered not only as a mass full of organs, but also as an object which evokes an awareness about the cultural conditions and sexualities. We discussed some definitions about body and its relation with the homoerotism, primarily, oriented to its expression in literature. We used the concepts from Goelnner (2003), Louro (2004) to observe the several images of the bodies suggested by the expressions emphasized in the poems, focusing the "young body", the "body virile" and the "tall body", main categories from Botto's lirical subject. In the end of this study, we understand that the homoerotic relationships in As Canções de António Botto are made through the poetic language from the imagery and linguistic expressions that compose the semantic field of homoerotic subjects. Thus, a lyricism considered silenced theretofore - the "homoerotic lyricism". We also note that the poems are led by a emotional speech, made by confessions from his love relationships with people of same sex, maily younger men, which sometimes they assume the function of rentboys, according to Perlongher's (2008) points of view, which love relationships are often limited to a only one meetin, setting as a "pure love", according to Bauman.